2012
DOI: 10.1177/1086026612445390
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Pathways Into Activism

Abstract: This article explores women’s pathways to participation in environmental justice advocacy in California’s San Joaquin Valley. Many scholars find that women become environmental justice activists according to a common set of experiences in which apolitical women personally experience an environmental problem that launches them into a life activism to protect the health of their families. Although a small group of the 25 women the author interviewed fit this description, overall the interviews reveal a much more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The most notable examples, include Perkins 2015 [9], Perkins 2012 [10], Bell 2013 [11], Bell 2010 [12], Buckingham and Kulcur 2009 [13], Kurtz 2007 [14], Nightingale 2006 [6], Sze 2004 [15], Sze 2006 [16], Verchick 2004 [17], Warren 1991 [18], Platt 1997 [19], Kirk 1997 [20] and Krauss 1993 [21] among others mentioned in this paper. Buckingham and Kulcer [13] consider that this may be because women are not necessarily found in specific or segregated geographic locations.…”
Section: Introductionmentioning
confidence: 99%
“…The most notable examples, include Perkins 2015 [9], Perkins 2012 [10], Bell 2013 [11], Bell 2010 [12], Buckingham and Kulcur 2009 [13], Kurtz 2007 [14], Nightingale 2006 [6], Sze 2004 [15], Sze 2006 [16], Verchick 2004 [17], Warren 1991 [18], Platt 1997 [19], Kirk 1997 [20] and Krauss 1993 [21] among others mentioned in this paper. Buckingham and Kulcer [13] consider that this may be because women are not necessarily found in specific or segregated geographic locations.…”
Section: Introductionmentioning
confidence: 99%
“…Decades of environmental justice organizing and research by allied environmental health scientists throughout the SJV have helped to bring increased state-level regulatory scrutiny to the inadequate and exclusionary development patterns, environmental policies, and decision making processes in the SJV. Advocates and allies have targeted these developments, policies, and processes because they have placed vulnerable residents and communities at increased risk of exposures to toxic air pollution and other hazardous substances in the SJV [69,70,71,72,73,74,75,76,77,78,79].…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing complexity of the current global social environment (e.g., migration crises, widening gap between rich and poor, etc. ), the distribution and use of urban green spaces are increasingly showing inequality and spatial segregation [14,15]. Currently, the justice of PGS in high-density urban areas is an important issue in the field of social justice, with major implications for public health and social integration [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that there are differences in the degree to which different groups use PGS [21][22][23][24][25]. Green space inequity is mostly impacted by income, racial characteristics, age, gender, and low residential area groups [15,[22][23][24][26][27][28]. Social status can also impact green inequity, with migrants disadvantaged in their access to urban green space and differences in social background, culture and language potentially preventing migrant groups from using parks for daily communication and activities [29].…”
Section: Introductionmentioning
confidence: 99%